Metadata and semantics research : 8th Research Conference, MTSR 2014, Karlsruhe, Germany, November 27-29, 2014. Proceedings - Studer, Rudi; Garoufallou, Emmanouel; Sicilia, Miguel-Angel; Closs, Sissi (Communications in Computer and Information Science, 2014)
This book constitutes the refereed proceedings of the 8th Metadata and Semantics Research Conference, MTSR 2014, held in Karlsruhe, Germany, in November 2014. The 23 full papers and 9 short papers presented were carefully reviewed and selected from 57 submissions. The papers are organized in several sessions and tracks. They cover the following topics: metadata and linked data: tools and models; (meta) data quality assessment and curation; semantic interoperability, ontology-based data access and representation; big data and digital libraries in health, science and technology; metadata and semantics for open repositories, research information systems and data infrastructure; metadata and semantics for cultural collections and applications; semantics for agriculture, food and environment.